2010
DOI: 10.1021/bi101256x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Evolution of Inverted-Topology Repeats from LeuT-Fold Transporters Using AlignMe

Abstract: X-ray crystal structures have revealed that numerous secondary transporter proteins originally categorized into different sequence families share similar structures, namely, the LeuT fold. The core of this fold consists of two units of five transmembrane helices, whose conformations have been proposed to exchange to form the two alternate states required for transport. That these two units are related implies that LeuT-like transporters evolved from gene-duplication and fusion events. Thus, the origins of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
108
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 59 publications
1
108
2
Order By: Relevance
“…It is important to note that the evolutionary relationship of the DedA and LeuT families is derived not from amino acid content but from hydrophobicity profiles and therefore would not turn up in a simple BLAST search. The data from the study by Khafizov et al also suggest that DedA family proteins may adopt dual topologies in the membrane (8).…”
Section: Putative Functions For Deda Family Membersmentioning
confidence: 96%
See 2 more Smart Citations
“…It is important to note that the evolutionary relationship of the DedA and LeuT families is derived not from amino acid content but from hydrophobicity profiles and therefore would not turn up in a simple BLAST search. The data from the study by Khafizov et al also suggest that DedA family proteins may adopt dual topologies in the membrane (8).…”
Section: Putative Functions For Deda Family Membersmentioning
confidence: 96%
“…An analysis of protein evolutionary relationships using a novel software program called AlignMe revealed that bacterial DedA family proteins may share structural motifs with the LeuT protein superfamily (8). LeuT is a bacterial homolog of the neurotransmitter sodium symporter (75) and vSGLT of the solute:sodium symporter family.…”
Section: Putative Functions For Deda Family Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…This fold is shared by transporters of several different families (1). Structural studies of different "5 ϩ 5" transporters, including the bacterial Na ϩ /amino acid symporter LeuT, have provided major insights into the successive conformations adopted by this category of transporters during substrate transport via an alternative access mechanism (1,12,13).…”
mentioning
confidence: 99%
“…The FIRL-fold is characterized by an internal twofold pseudosymmetry, with an axis running parallel to the membrane plane through the center of the transporter relating the first five transmembrane (TM) helices to the second set of five TM helices, so that their TM topologies are inverted with respect to one another (12,14). Because some of these transporters also contain additional TM helices either preceding or following the 5-TM repeat (N-or C-terminal helices, respectively), for simplicity of comparison we introduce a numbering scheme for the repeated helices, namely A1-5 for TM helices of the first repeat and B1-5 for helices belonging to the second repeat (Fig.…”
mentioning
confidence: 99%